THE ASYMMETRIC EFFECTS OF FISCAL POLICY SHOCKS ON PRIVATE CONSUMPTION IN SAUDI ARABIA - Alwagdani, Othman (European Scientific Journal, ESJ, 2014)
The objective of this paper is to examine the asymmetric effects of exogenous fiscal policy shocks on the level and grow rate of private consumption is Saudi Arabia during the period 1973-2011. In this respect, fiscal policy variables are disaggregated into government capital and current expenditures, and the associated innovations are decomposed into expansionary (positive) and contractionary (negative) shocks. Both models agree on the following conclusions. First, expansionary government capital and current expenditures stimulate private consumption and lift up the optimism level of private agents. Second, negative shocks tend to be larger in magnitude than positive ones, indicating that private consumption is not flexible enough to vary symmetrically with fiscal policy. In case of contractionary shocks, the results are mixed. With regards to the first model with level specifications, the empirical evidence supports the presence of asymmetric and crowing in effects of fiscal shocks. On the other hand, the second model agrees in a temporary fashion with the neoclassical view and ecrowding-out effects.